Mengulik Seni Tafsir: Menganalisis Teknik Dan Ragam Metode Dalam Tafsir - Umar Al Faruq; Noni Sherlya Yasmin Ramadhani; Nimas Ifthinatun Nabila; Wahyu Adi Nugroho (CV. ITTC INDONESIA, 2024)
Tafsir of the Qur’an is defined as a scientific discipline that is very important for understanding the teachings of the Islamic religion. In this context, methodological approaches play a crucial role in the process of interpreting sacred texts. This article has the vision to explore various exegetical methods applied in the context of the study of Al-Qur’an exegesis. Through a comprehensive literature review, this article examines the importance of selecting the appropriate interpretation method according to the context of the text and the purpose of interpretation. Various approaches such as linguistic interpretation, historical interpretation, and contextual interpretation are explored to enrich understanding of sacred texts. In addition, this article also discusses the implications of using certain interpretive methods in the contemporary context and offers suggestions for the development of more inclusive and diverse interpretive methodologies. It is hoped that this article can contribute maximally to efforts to understand the importance of methodological approaches in the interpretation of the Al-Qur’an and become a basis for further research in this field.